Market Structure and Competition of Indonesian Cocoa Beans Exports in the Malaysian Market - Yafi, Muhammad Ali; Wirda, Bunga; Adyanti, Amanda Sekar (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Indonesian cocoa is leading commodity that is able to export to other countries such as Malaysia. Exporting countries compete with each other for the Malaysian market, even though world demand for cocoa beans continues to increase. The study aims to identify the competitive position, elasticity, and market structure of Indonesian cocoa beans and exporting countries in the Malaysian market. The research data source is secondary from ITC Trade Map, from January 2017 to December 2023. The variables used are the value and quantity of cocoa bean exports from 8 exporting countries in Malaysia. The analytical used are Almost Ideal Demand System (AIDS) approach to determine level of competition and Herfindahl-Hirschman Index (HHI) and Concentration Ratio (CR) analyses to see market structure. The results of the HHI show that cocoa bean exports in the Malaysian have a high degree of market concentration, with CR4 reaching 71% and CR8 reaching 91%. The AIDS results that expenditure elasticity is negative, indicating that Indonesian cocoa beans are inferior good. The elasticity itself is negative, indicating that Indonesian cocoa beans are inelastic. Cross price elasticity, Indonesia has substitution relationship with Ecuador, Ghana, and Cameroon, and complementary relationship with Côte d'Ivoire, Nigeria, Papua NG, and Uganda.